When Technology Meets Transparency & Accountability: A Strategy to Prevent Corruption in Local Government - Cahyani, Tinuk Dwi; Kurniawan, Wahyudi; Nuryasin, Ilyas; Rismara, Nabila Aprilia; Ujilast, Farhan Alif (Faculty of Law, University of Muhammadiyah Malang, 2026)
This study aims to develop an information technology–based transparency and accountability model to support corruption prevention in local government procurement in Batu City, East Java, Indonesia. Adopting a qualitative approach, this study combines a literature review with data collected through Focus Group Discussions (FGDs) involving Batu City Government’s officials and village leaders. Data were analysed using NVivo 12 Plus to identify recurring patterns and key themes related to governance, technology, and integrity. The findings reveal that although Batu City has promoted digitalisation through agency-specific applications, the absence of an integrated cross-agency procurement system creates oversight gaps and accountability risks. The study highlights that effective IT-based procurement systems require not only data integration and open budget information but also reliable human resource integrity and ethical commitment. Advanced digital systems alone are insufficient without a robust anti-corruption culture. This study proposes an integrated information-technology model for goods and services procurement to help enhance budget transparency, accelerate anomaly detection, improve procurement traceability, and strengthen digital evidence for law enforcement. The proposed model serves as a strategic and sustainable oversight instrument, thereby reinforcing regional anti-corruption enforcement frameworks.